2016
DOI: 10.1037/pag0000095
|View full text |Cite
|
Sign up to set email alerts
|

Stressor diversity: Introduction and empirical integration into the daily stress model.

Abstract: The present study examined if and how stressor diversity, the extent to which one’s stressor events are spread across multiple types of stressors, contributes to daily affective well-being through the adult life span. Stressor diversity was examined as a unique predictor of daily affect and as a moderator of stressor exposure and stressor reactivity effects. Analyses span two independent studies of daily stress: the National Study of Daily Experiences with N=2,022 adults, aged 33–85, assessed over T=8 days, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 80 publications
(161 reference statements)
7
59
1
Order By: Relevance
“…Researchers have found that under high stress exposure, individuals influenced by stressors focused on a few areas tended to experience less positive affect and more negative effect daily as compared to those with stressors spread out to more areas (Koffer et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have found that under high stress exposure, individuals influenced by stressors focused on a few areas tended to experience less positive affect and more negative effect daily as compared to those with stressors spread out to more areas (Koffer et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, from the chronicity of stressor perspective, low stressor diversity is more likely to be associated with low positive affect and high negative affect as individuals with stressors concentrating on a few areas have less coping options as compared to those with stressors spreading throughout more areas (e.g., Koffer et al, 2016). Koffer et al (2016) extracted and analyzed data from two independent studies, National Study of Daily Experiences (2,022 adults) and The Intraindividual Study of Affect, Health, and Interpersonal Behavior (150 adults). Both studies collected self-report data on daily stressors and daily affect.…”
Section: Stress and Stressor Diversitymentioning
confidence: 99%
See 3 more Smart Citations